Pengaruh Nilai Tukar Terhadap Pertumbuhan Ekonomi di Indonesia - Wailul Saputri; Dwi Hasmidyani; Levia Ega Berliani; Ria Gustini; Muhammad Akbar Budiman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Global economic issues have significantly impacted national economic progress in recent decades, especially for developing countries such as Indonesia. Currency exchange rates are one of the main variables that influence this economic process. The performance of a country's external sector is largely determined by the exchange rate, which also affects a number of other macroeconomic factors. The purpose of this study is to see how much Indonesia's economic growth is affected by the exchange rate between 1980 and 2023. Data from government agencies including the Central Bureau of Statistics and Bank Indonesia are used in this quantitative approach using a literature study approach. The findings show that changes in the value of the rupiah, especially when depreciation occurs, have a significant influence on a number of economic factors, such as imports, exports, inflation, domestic investment, and consumption. The competitiveness of Indonesian export goods in the global market increases with the depreciation of the exchange rate. At the same time, however, it also leads to higher prices for imported goods, increases the burden of foreign debt, and depresses people's purchasing power and domestic investment activity. The last five years of data reflect the fluctuating pattern of Indonesia's international trade, which is closely related to exchange rate conditions and global economic dynamics. Exchange rate instability creates economic uncertainty, which can hamper long-term growth. Therefore, stabilizing the exchange rate and strengthening the export sector are important strategies, supported by monetary and fiscal policies that are adaptive to global changes.